Kepemimpinan Kharismatik Tuan Guru Sebagai Pemoderasi Determinan Pengelolaan Keuangan Pada Akuntabilitas Pondok Pesantren - Pituringsih, Endar; Basuki, Prayitno; Akram, Akram (E-Jurnal Akuntansi, 2023)
This study aims to analyze the effect of human resource capability and treasurer ethics moderated by the charismatic leadership of the teacher on financial management and the implications for the accountability of Islamic boarding schools. The research was conducted at Islamic boarding schools throughout Lombok Island, West Nusa Tenggara Province. The total population in the study was 558 Islamic boarding schools. Determination of the sample using purposive sampling method with the Slovin formula. The results of the study show that human resource capability and treasurer ethics have an effect on financial management. The charismatic leadership of the guru does not moderate human resource capabilities, but moderates the treasurer's ethics towards financial management. And financial management influences the accountability of Islamic boarding schools. Keywords: Human Resource Capability; Treasurer Ethics; Tuan Guru Charismatic Leadership; Financial Management; Islamic Boarding School Accountability